Association of Time of Day With Outcomes Among Patients Triaged for a Suspected Severe Stroke in Nonurban Catalonia. Issue 3 (28th February 2023) - García-Tornel, Álvaro; Flores, Alan; Terceño, Mikel; Cardona, Pedro; Amaro, Sergi; Gomis, Meritxell; Zaragoza, Josep; Krupinski, Jerzy; Gómez-Choco, Manuel; Mas, Natalia; Cocho, Dolores; Catena, Esther; et al.
Abstract : Background: We aim to assess whether time of day modified the treatment effect in the RACECAT trial (Direct Transfer to an Endovascular Center Compared to Transfer to the Closest Stroke Center in Acute Stroke Patients With Suspected Large Vessel Occlusion Trial), a cluster-randomized trial that did not demonstrate the benefit of direct transportation to a thrombectomy-capable center versus nearest local stroke center for patients with a suspected large vessel stroke triaged in nonurban Catalonia between March 2017 and June 2020. Methods: We performed a post hoc analysis of RACECAT to evaluate if the association between initial transport routing and functional outcome differed according to trial enrollment time: daytime (8:00 am –8:59 pm ) and nighttime (9:00 pm –7:59 am ). Primary outcome was disability at 90 days, as assessed by the shift analysis on the modified Rankin Scale score, in patients with ischemic stroke. Subgroup analyses according to stroke subtype were evaluated. Results: We included 949 patients with an ischemic stroke, of whom 258 patients(27%) were enrolled during nighttime. Among patients enrolled during nighttime, direct transport to a thrombectomy-capable center was associated with lower degrees of disability at 90 days (adjusted common odds ratio [acOR], 1.620 [95% CI, 1.020–2.551]); no significant difference between trial groups was present during daytime (acOR, 0.890 [95% CI, 0.680–1.163]; P interaction =0.014). Influence of nighttime on the treatment effect was only evident in patients with large vessel occlusion(daytime, acOR 0.766 [95% CI, 0.548–1.072]; nighttime, acOR, 1.785 [95% CI, 1.024–3.112] ; P interaction <0.01); no heterogeneity was observed for other stroke subtypes ( P interaction >0.1 for all comparisons). We observed longer delays in alteplase administration, interhospital transfers, and mechanical thrombectomy initiation during nighttime in patients allocated to local stroke centers. Conclusions: Among patients evaluated during nighttime for a suspected acute severe stroke in non-urban areas of Catalonia, direct transport to a thrombectomy-capable center was associated with lower degrees of disability at 90 days. This association was only evident in patients with confirmed large vessel occlusion on vascular imaging. Time delays in alteplase administration and interhospital transfers might mediate the observed differences in clinical outcome. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02795962.